Conceptualizing and Evaluating the Healthy Orthorexia Dimension - Da Silva, Wanderson Roberto [UNESP]; Neves, Angela Nogueira; Donofre, Giovanna Soler [UNESP]; Bratman, Steven; Teixeira, Paula Costa; Campos, Juliana Alvares Duarte Bonini [UNESP] (Springer Nature, 2023)
Orthorexia can be understood as a drive for eating foods perceived to be healthpromoting. When this drive includes obsessive thoughts and rigid behaviors about food choices, a person can suffer physical, psychological, and social harms. In the literature, this symptomatology is known as orthorexia nervosa, as it can cause damage in different areas of people’s lives. On the other hand, a drive for healthy eating can also be experienced as a guide to help people make food choices aiming to establish a health-promoting eating habit. This has been named in the literature as healthy orthorexia, but it is not clearly understood yet. The aim of this chapter was to conceptualize healthy orthorexia and explore its forms of evaluation, providing discussion about empirical evidence and practical implications. For that, a background about orthorexia nervosa was also necessary to understand how healthy orthorexia fits into this phenomenon that is still under debate in the clinical and scientific community.
Keywords: Behavior; Diagnostic Criteria; Disorder; Eating; Fixation; Focus; Healthy; Interest; Nervosa; Non-pathological; Obsession; Orthorexia; Pathological; Preoccupation; Scales